Democracia ambiental em Parauapebas-PA: mecanismos participativos para promoção de direitos de acesso em matéria ambiental - Petrilli, Leonardo (2024)
Environmental democracy has within its scope the rights of access to information, participation and environmental justice. These precepts are at the heart of the Ecological State of Law and are intertwined at the intersection between human rights and the right to the environment. In this sense, the research carried out an investigation into environmental democracy in the mining municipality of Parauapebas-PA, with the experimentation of a more popular and diffuse participatory instrument, aiming at a new arrangement in environmental participation. Through action research, some instruments were used to collect and produce data, which provided elementary conditions to raise the main debate established by the study. A survey was carried out among the local population and interviews with the Executive Public Power - procedures that provided subsidies for the construction of a diagnosis of social participation at the local level using the “C.L.E.A.R Tool”, a methodology developed for the European Commission. Subsequently, public hearings were held together with the Public Ministry of the State of Pará to debate the main environmental challenges highlighted by the population. The research results demonstrate that the absence of legitimate formal structures to develop and operationalize access rights in environmental matters, as well as at the federal level, also occurs in the municipality of Parauapebas. The diagnosis revealed that the municipality does not have community and civic spirit and programs to support participation. Furthermore, the research showed that environmental information is neglected and centralized in the head of the executive branch. The results also reveal that the forum established with the facilitation of the Public Ministry and the participation of the specialized Public Power, in addition to civil society and academia, is successful as a space for exercising participatory democracy and provided conditions for suggestions of public policies necessary for the guarantee of environmental access, such as the creation of space to strengthen social movements and community culture, establishment of commissions for articulation and representation of people and communities, strengthening of neighborhood organizations, establishment of routines and spaces for social listening and the creation of an education program for citizens and civil servants for social participation. Thus, the research showed that the population in this municipality in the Amazon of Pará is more responsive to the democratic institution than the public authorities and that forums and spaces for social participation produce important narratives and contribute to the construction of more assertive public governance.